2021
DOI: 10.1186/s13073-021-00851-9
|View full text |Cite
|
Sign up to set email alerts
|

Trans-ethnic gut microbial signatures of prediabetic subjects from India and Denmark

Abstract: Background Recent studies have indicated an association of gut microbiota and microbial metabolites with type 2 diabetes mellitus (T2D). However, large-scale investigation of the gut microbiota of “prediabetic” (PD) subjects has not been reported. Identifying robust gut microbiome signatures of prediabetes and characterizing early prediabetic stages is important for the understanding of disease development and could be crucial in early diagnosis and prevention. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 89 publications
3
28
0
Order By: Relevance
“…The genus streptococcus was widely found in nature, human and animal stools, and healthy people's nasopharynx and intestines, which can mainly cause suppurative in ammation, toxin diseases and hypersensitivity reactive diseases. It was also reported in diabetes in previous studies [23]. In our study, there were two prevotella genera in bacterial abundance and clinical indicators, which is the result of the current Greenggenes database.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The genus streptococcus was widely found in nature, human and animal stools, and healthy people's nasopharynx and intestines, which can mainly cause suppurative in ammation, toxin diseases and hypersensitivity reactive diseases. It was also reported in diabetes in previous studies [23]. In our study, there were two prevotella genera in bacterial abundance and clinical indicators, which is the result of the current Greenggenes database.…”
Section: Discussionsupporting
confidence: 84%
“…This effect seems to be related to the enhancement of the metabolic pathways including terpenoid-quinone, lipopolysaccharides and N-glycan biosynthesis [22]. The genus Alistipes is also very important in the diabetic group, and the effect of the genus Alistipes on diabetes has also been reported recently [23]. The genus Alistipes is currently considered to be a bacterium that produces short-chain fatty acids (SCFA), which have a number of potential roles in modulating metabolic health and DM risk factors, such as blood glucose regulation and metabolic regulation, and maintaining the integrity of the intestinal barrier [24].…”
Section: Discussionmentioning
confidence: 89%
“…In the study of gene expression of the bacteria found that more than half of the genes involved in the complex of Mycoloyl-arabinogalactan-peptidoglycan [ 33 ]. A study analyzed the gut microbime of 144 prediabetic subjects [ 34 ] and found that the relative abundance of Nocardiaceae and Rhodococcus was significantly increased. Studies have found that polycystic ovary syndrome (PCOS) is closely related to metabolic syndrome, especially insulin resistance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human data on postbiotics and DM are lacking, and we identified only one trial on this topic in healthy adults [85]. It is likely that ethnic group [138,139], sex [140], and the time course of DM [141] influence the GM response to postbiotic treatments, and these aspects should be contemplated in human studies. Many of the included studies did not analyse the changes in the GM following the interventions, and this would provide valuable information about the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%